Rheological characteristics of mixture of raw primary and thickened excess activated sludge: impact of mixing ratio, solid concentration, temperature and sludge age - Hong, Eugene; Yeneneh, Anteneh; Sen, Tushar; Ang, Ming; Kayaalp, A.; Kayaalp, M. (2015)
Wastewater treatment process generates large quantities of sludge from different operational steps. The rheological behaviour of sewage sludge at different steps of wastewater treatment plant is useful for the design, operation, optimization of polymer dosing, hydrodynamics and mixing of anaerobic digestion and for efficient sludge management. In this research work, the impacts of solid concentration, temperature, mixing ratio and ageing of sludge on the rheological behaviour of mixture of raw primary and thickened excess activated sludge (TEAS) (mixed sludge) were investigated. Solid concentration, temperature, primary to TEAS mixing ratio, and sludge age were found to affect the viscosity, yield stress, flow index and flow consistency of mixed sludge. The decrease in total solid (TS) concentration of mixed sludge from 30 to 20 g/L resulted in significant decrease of yield stress from 7.4 to 1.1 Pa (85% reduction). The decrease in mixing ratio of TEAS to raw primary sludge from 80 to 20% resulted in the decrease of yield stress from 10.2 to 1.2 Pa confirming the significant contribution of TEAS to the non-Newtonian viscoplastic flow behaviour of the mixture. Similarly, viscosity also showed a decreasing trend with decreasing TS concentration and percentage of TEAS in the mixture. In contrast, yield stress and viscosity generally showed reduction with increasing temperature. Low temperature storage duration (sludge age) also affected the rheology of mixed sludge. The applicability of various rheological models such as Bingham, power law (Ostwald), Herschel-Bulkley, Casson, Sisko, Careau and Cross models were tested by fitting the models with experimental rheological characteristic of mixed sludge under various physico-chemical process conditions. The rheological data from the best fitted Bingham plastic and Sisko models are also discussed here.